2010
DOI: 10.1159/000314358
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption in Southern Sweden after Major Decreases in Danish Spirits Taxes and Increases in Swedish Travellers’ Quotas

Abstract: Background: In 2003, Denmark lowered its tax on spirits, and in 2004, Sweden increased its traveller import quotas. Aim: The aim of the study was to determine whether these two changes increased self-reported alcohol consumption in southern Sweden, which is located near Denmark. Method: Data were collected through telephone interviews with the general population between 2003 and 2006. Individuals aged 16–80 years were interviewed. Some lived in southern Sweden, others in the northern region, which was assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 14 publications
2
29
1
1
Order By: Relevance
“…Neither the longitudinal study nor the repeated cross-sectional studies based on surveys showed any increase in average volume of consumption or in binge drinking for any country, or for any major subgroups within countries, in short or medium term, whether or not a comparison to northern Sweden was made (Grittner, Gustafsson, & Bloomfield, 2009;Gustafsson, 2010aGustafsson, , 2010bMustonen, Mäkelä, & Huhtanen, 2007). This basic conclusion was still the same after controlling for effects of regression to the mean (Ripatti & Mäkelä, 2008) and modelling the effects of dropouts (Grittner et al, 2011;Ripatti & Mäkelä, 2007).…”
Section: Self-report Datamentioning
confidence: 96%
“…Neither the longitudinal study nor the repeated cross-sectional studies based on surveys showed any increase in average volume of consumption or in binge drinking for any country, or for any major subgroups within countries, in short or medium term, whether or not a comparison to northern Sweden was made (Grittner, Gustafsson, & Bloomfield, 2009;Gustafsson, 2010aGustafsson, , 2010bMustonen, Mäkelä, & Huhtanen, 2007). This basic conclusion was still the same after controlling for effects of regression to the mean (Ripatti & Mäkelä, 2008) and modelling the effects of dropouts (Grittner et al, 2011;Ripatti & Mäkelä, 2007).…”
Section: Self-report Datamentioning
confidence: 96%
“…Stafström [60] reports an increase in binge drinking by Swedish students, but a decline for intoxication. Organized by age group, the results indicate the following: (1) Denmark-binge drinking did not increase for any major adult subgroup [11] and drunkenness declined significantly among 15-year-old boys [29]; (2) Finland-no changes in adult bingeing using NTS data [11,50] or among youth [25,51], but selective increases among adults using other survey data [31]; (3) Hong Kong-decline in binge drinking among adults [13,33]; (4) Swedenyounger binge drinkers reduced alcohol use [11,43] and bingeing declined generally, with exceptions [42,41,60,61,59]; and (5) Switzerland-adult binge drinking changed little [27].…”
Section: Binge Drinkingmentioning
confidence: 97%
“…A variety of statistical methods are applied in primary studies, but a basic method is comparisons of before-after averages, with data divided into categories for age, gender, socioeconomic status, beverage, initial drinking-level or pattern, control site, and so forth. In some studies, hundreds of comparisons are possible [43,34]. In what follows, we first organize results by country, and present within-country summaries for drinking and drinking patterns.…”
Section: Policy Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a central motive for studying biomedical alcohol research in more detail, both in Sweden and in other countries i . In general, social research on alcohol policy is concerned with studying specific aspects of policy, such as analysing how control policies affect drinking and alcohol problems in specific population groups (e.g., Paschall et al, 2009), countries (e.g., Bloomfield et al, 2010), or parts of a country (e.g., Gustafsson, 2010), or studying one country's position in international policy-making (for Sweden, see Cisneros Örnberg, 2009). Whereas the liberalization of alcohol policy has been the topic for discussion in several studies (e.g., Johansson, 2008;Olsson, 2000;Sulkunen, 2000), biomedical alcohol research has received little attention.…”
Section: Aimsmentioning
confidence: 99%